DETECTING OF INDICATION FINANCIAL STATEMENT FRAUD - Darma, Jamaludin; Yahya, M. Rizal (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2023)
This study aims to determine the percentage of manufacturing companies categorized as manipulators, non-manipulators, or gray companies from 2016 to 2020. This study uses the Beneish M-Score index ratio as a data analysis technique. The population comprises 198 manufacturing companies listed on the IDX during that period, with a final sample size of 90 companies. Simple random sampling is used for the research sample. The findings reveal the following percentages for each category: In 2016, manipulators accounted for 19.05%, non-manipulators for 80.95%, and there were no gray companies. In 2017, manipulators constituted 42.86%, non-manipulators 57.14%, with no gray companies. For 2018, manipulators were 47.62%, non-manipulators 52.38%, and no gray companies. In 2019, manipulators were 26.19%, non-manipulators 73.81%, and no gray companies. Finally, in 2020, manipulators accounted for 30.95%, non-manipulators for 66.67%, and gray companies for 2.38% of the sample. These findings provide valuable insights into the distribution of manipulator, non-manipulator, and gray companies within the manufacturing sector over the specified five-year period.